The merozoite-specific protein, TgGRA11B, identified as a component of the Toxoplasma gondii parasitophorous vacuole in a tachyzoite expression model. Issue 10 (September 2017) - Ramakrishnan, Chandra; Walker, Robert A.; Eichenberger, Ramon M.; Hehl, Adrian B.; Smith, Nicholas C.
Graphical abstract: Highlights: Merozoites of Toxoplasma uniquely express two dense granule proteins, TgGRA11A and 11B. TgGRA11A and 11B have no homology to any other characterised protein or protein domain. Tachyzoites of Toxoplasma were engineered to express the merozoite-specific TgGRA11B. TgGRA11B localises to Toxoplasma dense granules and parasitophorous vacuole membranes. Abstract: The apicomplexan, Toxoplasma gondii, infects all warm-blooded animals as intermediate hosts but only felids as definitive hosts. Dense granule proteins are critical for the survival of Toxoplasma within host cells but, whilst these proteins have been studied intensively in tachyzoites, little is known about their expression in the coccidian stages in the cat intestine. Transcriptomic profiling indicates that two putative dense granule proteins, TgGRA11A and TgGRA11B, are expressed uniquely in merozoites. Immunofluorescent microscopy of Toxoplasma -infected cat intestine and tachyzoites engineered to express TgGRA11B, reveals that it is a dense granule protein that traffics into the parasitophorous vacuole and its membrane.